The Global Demand for Alcoholic Beverages, 2010–2015: Price and Expenditure Elasticities. Issue 4 (8th August 2021) - Macedo, Anthony; Gouveia, Sofia; Rebelo, João
Abstract: This paper analyses the demand for the alcoholic beverages. Taking a worldwide sample of forty-four countries and data from 2010 to 2015, own-price, cross-price, income, and expenditure elasticities are computed from the estimation of a single equation and the almost ideal demand system (AIDS), using the seemingly unrelated regression estimation (SURE) approach. Based on the elasticities' estimations, the findings show that for wine, beer, and spirits consumption increases proportionally with total expenditure on alcoholic beverages (and income). Regarding their own price, the demand for the three beverages present a negative and inelastic behavior. Moreover, beer and spirits are imperfect substitutes of wine and vice-versa, while beer and spirits are complements.